Organic Photoredox Catalysts Exhibiting Long Excited-State Lifetimes - Jeong, Dong Yeun; You, Youngmin (Synlett, 2021)
Organic photoredox catalysts with a long excited-state lifetime have emerged as promising alternatives to transition-metal-complex photocatalysts. This paper explains the effectiveness of using long-lifetime photoredox catalysts for organic transformations, focusing on the structures and photophysics that enable long excited-state lifetimes. The electrochemical potentials of the reported organic, long-lifetime photocatalysts are compiled and compared with those of the representative Ir(III)- and Ru(II)-based catalysts. This paper closes by providing recent demonstrations of the synthetic utility of the organic catalysts.1 Introduction2 Molecular Structure and Photophysics3 Photoredox Catalysis Performance4 Catalysis Mediated by Long-Lifetime Organic Photocatalysts4.1 Photoredox Catalytic Generation of a Radical Species and its Addition to Alkenes4.2 Photoredox Catalytic Generation of a Radical Species and its Addition to Arenes4.3 Photoredox Catalytic Generation of a Radical Species and its Addition to Imines4.4 Photoredox Catalytic Generation of a Radical Species and its Addition to Substrates Having C≡X Bonds (X=C, N)4.5 Photoredox Catalytic Generation of a Radical Species and its Bond Formation with Transition Metals4.6 Miscellaneous Reactions of Radical Species Generated by Photoredox Catalysis5 Conclusions
Keywords: photoredox catalysis; organic photocatalysts; long lifetime; photoinduced electron transfer; organic transformations